Implementation of Student Management in Malaysian and Indonesian Special Education Middle Schools - Erine Zhellina; Abdul Huda; Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia and Malaysia are countries that build quality education in a sustainable manner. The quality of education, which is a measure of educational success, is related to the ability or intelligence of students. In order to be able to manage students in a special education secondary school, student management is needed. The research process uses qualitative methods with a multi-site research type design. Data collection techniques are by interview, observation, and documentation. The results of this study indicate that the management of students carried out in special education secondary schools both in Indonesia and in Malaysia is carried out in accordance with the regulations in force in each country, because the two schools that are used as research subjects are national schools in Malaysia and public schools in Indonesia so that the rules from the government must be fully implemented, the difference lies in the grouping of students where in Malaysia they are grouped permanently according to the type of skill interest while in Indonesia they are grouped based on the level and type of disability